Correlation between leadership ability and achieving styles of student-athletes of the University of the Philippines Los Banos - Robles, Selwyn C. (2014)
Sport is tremendous setting for leadership exploration and application. Leadership is a valuable skill. It develops strong working relationships, earn respect, and support peers which lead to greater opportunities and career growth. The specific objectives of this study were: (1) to compare the self-assessed leadership ability of student-athletes by gender and sports events; (2) determine the achieving styles of student-athletes by gender and sports events and (3) to analyze the correlation between self-assessed leadership ability and achieving styles of student-athletes. Participants were 139 (71 males, 68 females) student-athletes of the University of the Philippines Los Banos (UPLB) with a mean age of 18.20 years (SD=1.71). Data obtained from the questionnaire were tabulated, analyzed and interpreted through the use of descriptive statistics.
Results revealed that both male and female student-athletes demonstrated high level of leadership ability. Female student-athletes showed a higher rating over their male counterpart by 0.01%. The assessment of each sports event in leadership ability was distinct. Male student- athletes reported that collaborative achieving style was the most preferred achieving style and the least preferred achieving style was power achieving style, on the other hand, female student-athletes reported that entrusting achieving style was the most preferred achieving style while power achieving style was the least. There was a significant relationship between leadership ability and collaborative achieving style of the student-athletes (r=1.88, p<0.05). Sharing responsibility for group tasks and collaborating (collaborative achieving style) with teammates to achieve a common goal contributed to their leadership abilities.
Keywords: Sports psychology